BERKEBUN DAN SUBJECTIVE WELL-BEING WARGA NEGARA INDONESIA - Paramita, Anindya Dewi; Faradiba, Andi Tenri (Institut Agama Islam Negeri (IAIN) Manado, 2023)
ABSTRACTThe “stay-at-home” policy to prevent the spread of COVID-19 outbreak make individuals involved in several that can be done at home, one of them is gardening. The reason is simple, to prevent boredom. Gardening was found to reduce stress and depression and boost positive emotion. This study aims to explore the relationship between gardening activities and subjective well-being in people who work their garden out. Gardening activities were examined by several questions about their gardening activities carried out, meanwhile the level of subjective well-being was measured by two questions developed by ONS (Waldron, Tinkler & Hicks, 2010). There were as many as 868 participants involved voluntarily whose data were collected online. The result showed that the amount of time spent in the garden and the time spent doing the garden (gardening) is significantly positively related to evaluative and eudemonic components of well-being. The more time spent exposing themselves to greenery, individuals tend to feel more satisfied with their lives and feel their lives is meaningful.Keywords: gardening, subjective well-being, covid-19 ABSTRAKKebijakan berdiam diri di rumah untuk mencegah merebaknya wabah corona membuat individu terlibat dalam beberapa aktivitas yang dapat dilakukan di rumah, salah satunya adalah berkebun. Alasannya sederhana, yaitu mencegah rasa bosan. Akan tetapi, aktivitas berkebun ditemukan dapat menurunkan stress dan depresi dan meningkatkan emosi positif. Penelitian ini bertujuan mengetahui hubungan antara aktivitas berkebun dengan subjective well-being. Aktivitas berkebun diukur dengan memberikan pertanyaan terbuka tentang kegiatan berkebun yang dilakukan sedangkan dua pertanyaan yang dikembangkan oleh ONS (Waldron, Tinkler, dan Hicks, 2010) digunakan untuk mengetahui tingkat subjective well-being. Ada sebanyak 868 partisipan yang terlibat secara sukarela dalam penelitian yang pengumpulan datanya menggunakan kuesioner yang disebarkan secara daring. Hasilnya menunjukkan bahwa banyaknya waktu yang dihabiskan di kebun dan juga untuk berkebun berhubungan positif signifikan dengan komponen evaluative maupun eudemonic well being. Semakin banyak waktu yang dihabiskan untuk memaparkan diri dengan area hijau, individu cenderung merasa puas dengan hidupnya dan merasa hidupnya bermanfaat.Kata Kunci: Aktivitas berkebun, subjective well-being, Covid-19